2010
DOI: 10.1073/pnas.1005039107
|View full text |Cite
|
Sign up to set email alerts
|

Trans locus inhibitors limit concomitant polysaccharide synthesis in the human gut symbiont Bacteroides fragilis

Abstract: Bacteroides is an abundant genus of bacteria of the human intestinal microbiota. Bacteroides species synthesize a large number of capsular polysaccharides (PS), a biological property not shared with closely related oral species, suggesting importance for intestinal survival. Bacteroides fragilis, for example, synthesizes eight capsular polysaccharides per strain, each of which phase varies via inversion of the promoters located upstream of seven of the eight polysaccharide biosynthesis operons. In a single cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 17 publications
1
65
0
Order By: Relevance
“…These patterns of ELISA reactivity support a model in which the expression of the 260.8 epitope is relatively stable across isolates in a given sample, whereas expression of the 225.4 epitope is under phase variable control. Consistent with this model, homologs of UpxY and UpxZ, which help mediate phase variation of capsular polysaccharides in B. fragilis (42), are present in the 225.4 locus but not in the 260.8 locus.…”
Section: Resultsmentioning
confidence: 59%
“…These patterns of ELISA reactivity support a model in which the expression of the 260.8 epitope is relatively stable across isolates in a given sample, whereas expression of the 225.4 epitope is under phase variable control. Consistent with this model, homologs of UpxY and UpxZ, which help mediate phase variation of capsular polysaccharides in B. fragilis (42), are present in the 225.4 locus but not in the 260.8 locus.…”
Section: Resultsmentioning
confidence: 59%
“…The expression vector pMCL140, noted for its robust transcription levels of inserted genes (35), was a kind gift from Laurie Comstock (Channing Laboratory, Harvard Medical School). SmaI (New England BioLabs, Ipswich, MA) was used to linearize pMCL140.…”
Section: Methodsmentioning
confidence: 99%
“…In nearly all of the B. fragilis bacteria of this ecosystem, the PSG locus promoter was consistently oriented on. Our in vitro studies have shown that the UpgZ protein, encoded by the PSG region, has a very wide spectrum of inhibition, preventing the transcription of all PS biosynthesis loci except PSG and PSH (4). Due to the fact that nearly all of the B. fragilis isolates from subject 14 had the PSH biosynthesis locus promoter oriented off at all time points, we predict that nearly all of the B. fragilis bacteria of subject 14 consistently and exclusively expressed PSG over the year of study.…”
Section: Vol 79 2011 Longitudinal Analysis Of Human Gut Bacteroidalmentioning
confidence: 97%
“…The first, collectively designated the UpxY proteins, are transcriptional antitermination factors necessary to prevent premature transcriptional termination in the 5Ј untranslated region of each operon (3). The proteins encoded by the second gene of each locus are termed the UpxZ proteins and function to inhibit the transcriptional antitermination property of subsets of heterol-ogous UpxY proteins (4). The UpxZ proteins have differential inhibitory spectra, establishing a hierarchical mode of regulation.…”
mentioning
confidence: 99%